Embeddedness of Economic Actions in the Social Network: Study among of Local Genuine Entrepreneurship in Cirebon, West Java - Haryono Haryono; Mukhtar Mukhtar; Titik Sumarti; Didin S. Damanhuri; Sofyan Sjaf (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2022)
Economic activities in a social context can not be separated from social networking, for example, the networking between business actors. This study aims to find out the time-term of the businessmen's work, with whom they worked; and the impact of their networking. This research was conducted in Cirebon Regency West Java Province, Indonesia, for 6 months, from May to October 2019. Applying the qualitative method, this research found that: local entrepreneurs in the rattan business sector have been running for a long time. As a result of historical formation, there is a wide network between entrepreneurs and entrepreneurs with certain institutions and community structures. The map of economic network attachment in social networks shows the diversity of attachments between economic networks and social networks.